At war's end: Building peace after civil conflict - Paris, Roland (Cambridge University, 2013)
All fourteen major peacebuilding missions launched between 1989 and 1999 shared a common strategy for consolidating peace after internal conflicts : immediate democratization and marketization. This volume argues that transforming war-shattered states into market democracies is a basically sound idea, but that pushing the process too quickly can have damaging and destabilizing effects. A more sensible approach would first establish a system of domestic institutions capable of managing the disruptive effects of democratization and marketization, and only then phase in political and economic reforms as conditions warrant. Avoiding the problems that marred many peacebuilding missions in the 1990s will require longer-lasting, better-planned, and ultimately more intrusive forms of intervention in the domestic affairs of war-torn states.